Implementasi Internet of Things untuk Pemantauan Kondisi Air Hasil Destilasi Otomatis - Erdianto Ramadhan; Ibrahim Ibrahim; Gina Lova Sari (LPPM Poltek ST Paul, 2020)
The purpose of this research is to update the distillation system by designing an internet of things for monitoring water conditions, so that water conditions can be monitored via a smartphone. This design uses the Arduino Uno microcontroller as the main control of the distillation system and in designing the internet of things, it uses an ESP8266-01 module as a component of sending data from the system to the Blynk application on the smartphone. Monitoring water conditions in this distillation system, there are several conditions, namely, the condition of the pH content in the water, the water concentration (salt content) and it is also equipped with monitoring the water level in the reservoir. Based on the results of the tests carried out, the implementation of the internet of things for monitoring the condition of the distilled water is going well where there is no difference in the appearance of sensor parameters between the LCD and the Blynk application, but the ESP8266-01 module only has a maximum distance of 25 meters, as for the delay. The ESP8266-01 module with the system off condition has an average delay of 8 minutes at night, 10 minutes in the morning, and 12 minutes at night with a provider that has an average internet speed of 12Mb / s. From the data generated in the process of sending data from the system to the blynk application, it requires a bandwidth of 93B and an average of 57bps of input.